POLA PERDAGANGAN INDONESIA DENGAN EMPAT MITRA DAGANG UTAMA TAHUN 1990-2023 - Gina Andriana Br Sembiring; Wayan Sukadana (Adisam Publisher, 2025)
International trade has become a key driver of Indonesia's economic development, particularly through trade relations with major partners such as China, Japan, the United States, and Singapore. Over the past three decades, Indonesia’s trade pattern has shown a strong reliance on the export of raw commodities and the import of high value-added manufactured goods. This pattern reflects the characteristics of a developing country that is rich in natural resources but still faces limitations in industrial capacity and technological advancement. This study aims to explore the structure of Indonesia's trade from 1990 to 2023 and evaluate its alignment with the classical theory of comparative advantage. Using a descriptive quantitative approach, this research applies the Revealed Comparative Advantage (RCA) method developed by Balassa to measure the competitiveness of Indonesia's exports in raw materials and manufactured products. The data is analyzed based on HS Code classifications and sourced from UN Comtrade.0020The results show that Indonesia consistently has a comparative advantage in the export of raw commodities, with RCA values greater than 1, while most imported manufactured goods show RCA values less than 1, indicating low competitiveness in that sector. These findings suggest that Indonesia’s trade pattern remains consistent with the principle of comparative advantage—exporting goods that can be produced at lower opportunity costs and importing goods that are less efficiently produced domestically. However, the country’s dependence on raw material exports presents long-term challenges, especially in a global economy that increasingly emphasizes industrialization and technological innovation.